Determinación de la línea básica de resistencia de Spodoptera frugiperda Smith a los insecticidas abamectina, alfacipermetrina, thiodicarb y bifentrin - Contreras Chacha, Joselyn Nieves (2016)
SUMMARY The investigation was made in the laboratories of Entomology of the Ability of Agricultural Sciences of the Technical University of Babahoyo, located in Km. 7,5 of the road Babahoyo-Montalvo. Four insecticides of different chemical groups were used. The work determined the basic resistance line of Spodoptera frugiperda (Smith) to the insecticides Alfacipermethrin, Thiodicarb, Bifetrin and Abamectin, with the conduction of susceptibility bioassays and the selection of third instar larvae populations. The products were applied in the prothorax of the larvae in mother solutions and dosages in each insecticide, with a maximum evaluation time of 96 hours. Eight concentrations were used for each input, which ranged from 0.0-7 ug / larva, respectively. The response of the group of larvae (control) with feeding only was measured. The selection of the biological material was made during a single generation of larvae. It was concluded that the insecticide thiodicar the LD50 was 2.00067; For the insecticide alfacipermethrin the DL 50 which was obtained was 0.320884; In the abamectin insecticide the LD50 was 1.70342 and in the insecticide bifentrin it was 0.864843. All populations of all chemical groups used had 100% mortalities with the highest concentrations in the control at 24 hours post application, while the colonies selected with the lowest concentrations did not exceed 16% mortality. The witness had mean 2.32% mortality at the same time. The LD50 ranged from 2.3 times the commercial dose. The high levels of control indicate that insect larvae do not currently have mechanisms of resistance to these groups of insecticides. For this reason, strategies must be implemented for the management of resistance in S. frugiperda.